Selective Host Cell Death by Staphylococcus aureus: A Strategy for Bacterial Persistence - Missiakas, Dominique; Winstel, Volker (Frontiers in Immunology, 2021)
Host cell death programs are fundamental processes that shape cellular homeostasis, embryonic development, and tissue regeneration. Death signaling and downstream host cell responses are not only critical to guide mammalian development, they often act as terminal responses to invading pathogens. Here, we briefly review and contrast how invading pathogens and specifically Staphylococcus aureus manipulate apoptotic, necroptotic, and pyroptotic cell death modes to establish infection. Rather than invading host cells, S. aureus subverts these cells to produce diffusible molecules that cause death of neighboring hematopoietic cells and thus shapes an immune environment conducive to persistence. The exploitation of cell death pathways by S. aureus is yet another virulence strategy that must be juxtaposed to mechanisms of immune evasion, autophagy escape, and tolerance to intracellular killing, and brings us closer to the true portrait of this pathogen for the design of effective therapeutics and intervention strategies.